Calcium and strontium isotope systematics in the lagoon-estuarine environments of South Australia: Implications for water source mixing, carbonate fluxes and fish migration. (15th October 2018) - Shao, Yuexiao; Farkaš, Juraj; Holmden, Chris; Mosley, Luke; Kell-Duivestein, Isaac; Izzo, Christopher; Reis-Santos, Patrick; Tyler, Jonathan; Törber, Philip; Frýda, Jiří; Taylor, Holly; Haynes, Deborah; et al.
Abstract: This study uses Ca and Sr isotopes (δ 44/40 Ca and 87 Sr/ 86 Sr), coupled with elemental ratios, to better understand the water source apportionment and carbonate output in the Coorong, Lower Lakes and Murray Mouth Estuary, which represents the terminus of Australia's longest river system. The geochemistry of waters in the Coorong (i.e., North and South Lagoon) can be explained by mixing of three major components, including: (i) the Southern Ocean seawater, (ii) local freshwaters, and (iii) hypersaline lagoon waters, the latter significantly modified by ongoing evaporation and carbonate formation. The Sr and Ca isotope composition of the North Lagoon is indistinguishable from that of the Southern Ocean (i.e., normal salinity of ∼35 PSU), with the exception of transient freshwater input events that can temporarily lower the salinity to brackish levels. Interestingly, our results from the hypersaline South Lagoon (salinity up to ∼120 PSU) confirmed that the latter is highly evaporated brackish water (with ≥40% contribution from continent-derived waters), which has been additionally modified by in-situ carbonate precipitation. Importantly, our Ca isotope and elemental constraints showed that about 15–17% of the dissolved Ca 2+ in the South Lagoon has been removed as CaCO3 (primarily as aragonite). This in turn has implications for the local carbonate cycle and blue carbon studies, suggesting that the South Lagoon acts as a net sink for the dissolved inorganic carbon (DIC). Ca isotope data from the otoliths of smallmouth hardyhead fish species ( Atherinosoma microstoma ) collected in the Coorong indicate that δ 44/40 Ca is primarily controlled by biological processes (i.e., kinetic isotope fractionation effects related to growth rate), rather than by the Ca isotope composition of local lagoon waters. As to 87 Sr/ 86 Sr in otoliths, the latter confirmed the importance of continent-derived water sources in the Coorong, recorded over the life span of the fish. Overall, with suitable fossil carbonate archives (e.g., bivalve shells, foraminifera), our calibration of 87 Sr/ 86 Sr and δ 44/40 Ca in the modern hydrological system, with respect to a large salinity gradient (ranging from fresh to hypersaline, i.e., 0 to ∼120 PSU), implies potential future applications of these isotope tracers in carbonate-producing coastal systems, which include (i) tracing and apportioning different water sources, (ii) quantifying local carbonate outputs, and (iii) reconstructing paleo-salinity changes.